Pemahaman Fiqih Melalui Pembelajaran Qowaid Fiqhiyyah di Pesantren Imam Syafi’I Tulungagung - Khoir, Annisa Fatkhul (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
Abstract Islamic boarding schools use traditional works as sources of knowledge. Islamic boarding schools strive to give students with a solid foundation and fundamentals of fiqh in order to avoid misunderstandings. Understanding the Al-Qur'an is the first stage in learning fiqh, followed by understanding hadiths from the Prophet that deal with fiqh issues and works produced by fiqh experts. There must be sufficient planning so that reference books can match learning objectives. With so many fiqh books, it requires more time to assess each one. The purpose of this study is to compare fiqh learning with qowaid fiqhiyyah learning at the Imam Syafi'i Islamic Boarding School in Tulungagung, so that it can be used as a resource for other Islamic Boarding School Education Institutions when determining reference books for fiqh learning. This study used qualitative descriptive research. Data were collected by observation, documentation, and interviews. The Imam Syafi'i Islamic Boarding School employs Syaikh Abdurrahman bin Nashir As-Sa'diy's book